THU0727-HPR Comparison of kinesio tape application and manual lymphatic drainage on lower extremity oedema and functions after total knee arthroplasty. (12th June 2018) - Guney Deniz, H.; Kinikli, G.I.; Onal, S.; Sevinc, C.; Caglar, O.; Yuksel, I.
Abstract : Background: Significant trauma and muscular tightness often result during Total Knee Artroplasty (TKA) surgery and thus act to restrict tissue fluid movement resulting with lower extremity oedema. Kinesio Taping is applied directly on the skin for restoration of normal fluid perfusion, removing congestion of lymphatic fluid or haemorrhages. In addition manual lymphatic drainage (MLD) enhances blood circulation and stimulates the lymphatic movement and unblocks lymphatic territories. Objectives: The aim of the study was to investigate the effectiveness of Kinesio Taping and MLD in reducing postoperative oedema, pain and lower extremity functions in the early stage after TKA. Methods: Forty patients who underwent unilateral TKA were randomised as Kinesio Taping group (n=12), MLD group (n=13) and control group (n=15). For all patients, postoperative rehabilitation program included early mobilisation and physical therapy twice a day during the stay in orthopaedic traumatology department. On the second day after surgery, lymphatic correction method was used on the Kinesio Taping group patients and a standardised 30 min MLD treatment was applied to the MLD group patients. Control group received only physiotherapy treatment. Circumference measurements were applied on preoperatively and the second, third, fourth day and 6th weeks after surgery. Knee Injury and Osteoarthritis Outcome Score (KOOS) was used to determine the functional outcomes on the 6th weeks after surgery. Repeated measures analysis was used to determine the group by time differences between groups. Results: A significant group effect was observed for oedema difference (F(4, 42) =2.44, p=0.047) and pain levels (F(3, 54) =4.56, p=0.006) and post hoc testing demonstrated a significantly lower oedema and pain levels in the both Kinesio Taping and MLD compared to control group. There was no difference found between Kinesio Taping and MLD groups (p=0.933). KOOS results were better in Kinesio Taping and MLD groups when compared to control group (p=0.021). There was no difference in KOOS results between Kinesio Taping and MLD groups (p=0.851). Conclusions: Applications of both Kinesio Taping and MLD to remove congestion of lymphatic fluid at the early stage after TKA surgery were found affective in enhancing blood circulation and stimulating the lymphatic movement. In addition, Kinesio Taping and MLD were both effective on relieving pain and improving functional outcomes after TKA surgery. References: [1] Donec V, Kriščiūnas A. The effectiveness of Kinesio Taping® after total knee replacement in early postoperative rehabilitation period. A randomized controlled trial. Eur J Phys Rehabil Med2014;50(4):363–71. [2] Ebert JR, Joss B, Jardine B, Wood DJ. Randomized trial investigating the efficacy of manual lymphatic drainage to improve early outcome after total knee arthroplasty. Arch Phys Med Rehabil2013;94(11):2103–11. Disclosure of Interest: None declared